TINDAKAN PEMELIHARAAN GIGI TIRUAN PADA PASIEN YANG MEMAKAI GIGI TIRUAN DI KLINIK GIGI drg. MUSTAM E, BA, SKG, MM, DTS - Merry Thressia (Menara Ilmu, 2016)
The lack of public knowledge about the denture, especially in terms of the maintenance ofthe denture is not entirely the fault of the people themselves, but rather the lack of informationabout the maintenance of the denture, so many people who do not understand the importanceof the maintenance of the denture and the condition of the denture in use, denture very helpfulto health such as to improve the aesthetics of the teeth. For treatment we need beberapahalsuch as cleaning, maintaining and see the condition of the denture, and how to clean it and putit in a place such as in a glass of water, so that the denture is not easily damaged andconvenient to be used again.This type of research is descriptive which aims to determine the maintenance of the dentureand the condition of artificial teeth in patients, using questionnaires, data management is doneby a simple analysis through univariate analysis.Results showed that the level of knowledge denture maintenance, of the 30 respondentsare 12 people (40%) of respondents who have a high level of maintenance, and 17 (56.67%) ofrespondents who have a moderate level of maintenance and one person (3.33%) respondentswho have a low level of maintenance. Suggested to people who wear dentures, denture thatneeds to be preserved, as beneficial to the health of your teeth and mouth. In the use of denturerequires knowledge and care better.ABSTRAK